Evaluation of Potential Methane Generation in the Investigation of an Abandoned Contaminated Landfill in Santiago, Chile - Montalvo-Martinez, S (Assoc. Brasiliera de Eng. Quimica / Braz. Soc. Chem. Eng., 2016)
This study presents the environmental evaluation of an abandoned and potentially contaminated landfill using analyses for the presence of heavy metals and for methane generation potential. The site is located in the city of Santiago, Chile, and was used as a rural landfill for domestic, industrial and construction waste until 1978, but is now in a heavily urbanized area and surrounded by houses. Analyses performed on 24 samples taken in and around the site show Potential Methane Generation (PMG) values between 1.6% and 11.3% of maximum projected levels. These low values, compared to those of an active landfill, indicate that waste material stored in the site has a low capacity to generate methane. Concentrations of heavy metals in the surface and deep soil are similar to typical levels for these metals in normal soil, according to international USEPA standards, and do not present imminent risk to human health. The use of the PMG test technique for the study of the health risk of an abandoned landfill is a new contribution to the Chilean evaluation methodology and management program for Abandoned Sites with Potential Presence of Contaminants (SAPPC). As part of the environmental management strategy for the site, two of the five operable units studied were transformed into a park after this study.